Chemically induced enucleation of activated bovine oocytes: chromatin and microtubule organization and production of viable cytoplasts. Issue 6 (16th October 2014) - Saraiva, Naiara Zoccal; Oliveira, Clara Slade; Leal, Cláudia Lima Verde; de Lima, Marina Ragagnin; Del Collado, Maite; Vantini, Roberta; Monteiro, Fabio Morato; Niciura, Simone Cristina Méo; Garcia, Joaquim Mansano
Summary: As the standard enucleation method in mammalian nuclear transfer is invasive and damaging to cytoplast spatial organization, alternative procedures have been developed over recent years. Among these techniques, chemically induced enucleation (IE) is especially interesting because it does not employ ultraviolet light and reduces the amount of cytoplasm eliminated during the procedure. The objective of this study was to optimize the culture conditions with demecolcine of pre-activated bovine oocytes for chemically IE, and to evaluate nuclear and microtubule organization in cytoplasts obtained by this technique and their viability. In the first experiment, a negative effect on oocyte activation was verified when demecolcine was added at the beginning of the process, reducing activation rates by approximately 30%. This effect was not observed when demecolcine was added to the medium after 1.5 h of activation. In the second experiment, although a reduction in the number of microtubules was observed in most oocytes, these structures did not disappear completely during assessment. Approximately 50% of treated oocytes presented microtubule reduction at the end of the evaluation period, while 23% of oocytes were observed to exhibit the complete disappearance of these structures and 28% exhibited visible microtubules. These findings indicated the lack of immediate microtubule repolymerization after culture in demecolcine-free medium, a fact that may negatively influence embryonic development. However, cleavage rates of 63.6–70.0% and blastocyst yield of 15.5–24.2% were obtained in the final experiment, without significant differences between techniques, indicating that chemically induced enucleation produces normal embryos.